"Take My Bone Away?" Hypoxia and bone: A narrative review. Issue 2 (9th July 2020) - Hannah, Scott S.; McFadden, Sonyia; McNeilly, Andrea; McClean, Conor
Abstract: To maintain normal cellular and physiological function, sufficient oxygen is required. Recently, evidence has suggested that hypoxia, either pathological or environmental, may influence bone health. It appears that bone cells are distinctly responsive to hypoxic stimuli; for better or worse, this is still yet to be elucidated. Hypoxia has been shown to offer potentially therapeutic effects for bone by inducing an osteogenic–angiogenic response, although, others have noted excessive osteoclastic bone resorption instead. Much evidence suggests that the hypoxic‐inducible pathway is integral in mediating the changes in bone metabolism. Furthermore, many factors associated with hypoxia including changes in energy metabolism, acid–base balance and the increased generation of reactive oxygen species, are known to influence bone metabolism. This review aims to examine some of the putative mechanisms responsible for hypoxic‐induced alterations of bone metabolism, with regard to osteoclasts and osteoblasts, both positive and negative. Abstract : This review provides a detailed examination of the effects of hypoxia, hypoxia‐inducible factors (HIF) and other downstream effects on osteoclasts and osteoblasts. Hypoxia stimulates osteoclast activity and number while also inhibiting osteoblast activity and number through numerous mechanisms. Hypoxia induces HIF‐1 and HIF‐2 stabilisation, which exert differential effects on osteoclasts and osteoblasts, examined here within.